2016
DOI: 10.1016/j.jacc.2016.05.076
|View full text |Cite
|
Sign up to set email alerts
|

Cost Implications of Using Different ECG Criteria for Screening Young Athletes in the United Kingdom

Abstract: Contemporary ECG interpretation criteria decrease costs for de novo screening of athletes, which may be cost permissive for some sporting organizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 25 publications
1
32
1
4
Order By: Relevance
“…A population based observational study from Italy showed an 89% reduction in the incidence of sudden cardiac death following the introduction of mandatory pre-participation screening (from 3.6/100 000 to 0.4/100 000 person years over a 26 year period) 19. A UK study of 4925 young athletes identified an ECG abnormality in 4.3%, although only 0.3% had a potentially serious cardiac condition 20. ECG abnormalities can be subtle, however, and an athlete presenting with an abnormality should be assessed by a suitably trained physician.…”
Section: How Are Inherited Cardiomyopathies Detected?mentioning
confidence: 99%
“…A population based observational study from Italy showed an 89% reduction in the incidence of sudden cardiac death following the introduction of mandatory pre-participation screening (from 3.6/100 000 to 0.4/100 000 person years over a 26 year period) 19. A UK study of 4925 young athletes identified an ECG abnormality in 4.3%, although only 0.3% had a potentially serious cardiac condition 20. ECG abnormalities can be subtle, however, and an athlete presenting with an abnormality should be assessed by a suitably trained physician.…”
Section: How Are Inherited Cardiomyopathies Detected?mentioning
confidence: 99%
“…18 Initial screening with health questionnaire, physical examination and ECG was performed at a subsidised cost of $53 per athlete. Based on these preliminary findings, cardiologists requested secondary investigations (if applicable) to confirm or refute the presence of cardiac disease, the costs of which were calculated based on NHS tariffs in the UK.…”
Section: Uk Situationmentioning
confidence: 99%
“…Identification of athletes with potentially serious cardiac diseases plays an important role. Pre-participation screening with a 12-lead electrocardiogram (ECG) is effective and may rise suspicion for cardiomyopathies (4). Organizations and sports governing bodies, such as European Society of Cardiology, American Heart Association and International Olympic Committee are positive in the attitude of the obligatory pre-participation cardiovascular screening (5-7).…”
Section: Introductionmentioning
confidence: 99%